1981
DOI: 10.1037/h0086077
|View full text |Cite
|
Sign up to set email alerts
|

Variations in cognitive behavior modification for test anxiety.

Abstract: Meichenbaum's cognitive behavior modification treatment for test anxiety consists of a cognitive (insight) and a behavioral (modified desensitization) component. In the present experiment variations on the insight and the behavioral component of the program were examined. Subjects (N = 45) were randomly assigned to one of three treatment or two control groups. One group received Meichenbaum's cognitive behavior modification treatment. For a second group Meichenbaum's desensitization component was retained but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In addition, CT programs for test anxiety typically include relaxation techniques, such as deep breathing and guided imagery. Several studies have indicated that interventions based on CT principles produce a reduction in test anxiety (Dendato & Diener, 1986;Goldfried, Linehan, & Smith, 1978;Himle, Thyer, Papsdorf, & Caldwell, 1984;McCordick, Kaplan, Smith, & Finn, 1981;Meichenbaum, 1971). However, meta-analyses suggest that the full CT package for test anxiety was no better (Hembree, 1988) or was less effective (Ergene, 2003) than behavioral-only treatments.…”
Section: Treatments For Test Anxiety Cognitive Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, CT programs for test anxiety typically include relaxation techniques, such as deep breathing and guided imagery. Several studies have indicated that interventions based on CT principles produce a reduction in test anxiety (Dendato & Diener, 1986;Goldfried, Linehan, & Smith, 1978;Himle, Thyer, Papsdorf, & Caldwell, 1984;McCordick, Kaplan, Smith, & Finn, 1981;Meichenbaum, 1971). However, meta-analyses suggest that the full CT package for test anxiety was no better (Hembree, 1988) or was less effective (Ergene, 2003) than behavioral-only treatments.…”
Section: Treatments For Test Anxiety Cognitive Therapymentioning
confidence: 99%
“…Moreover, almost none of the studies examining CT principles have used measurements that can capture changes in real-world performance. Many studies examining CT's effects on test anxiety rely on analogue measures of performance, such as tests of general reasoning (Orbach, Lindsay, & Grey, 2007), speed tests with numbers (Finger & Galassi, 1977), or problem-solving tasks (McCordick et al, 1981); none of these studies revealed benefits to CT over behavioral-only (e.g., modeling, exposure) or control treatment conditions on performance measures. Furthermore, these tasks may not be reflective of real-world performance on examinations.…”
Section: Treatments For Test Anxiety Cognitive Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The posttreatment assessment package was administered at the final meeting of the treatment groups. 2 The dependent variables for all of the analyses to be reported are change scores (posttreatment score minus pretreatment score) except for the digit symbol task, which is an after-only measure. 3 ' 4…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Other authors have supported the use of similar multicomponent treatment packages designed to improve academic performance (Decker & Russell, 1981;Lent & Russell, 1978;McCordick, Kaplan, Smith, & Finn, 1981;Williams, Decker, & Libassi, 1983;Zimpfer, 1986). We have found this group program to be an effective intervention for underachieving students and a successful training experience for graduate students who are learning to be counselors.…”
Section: Discussionmentioning
confidence: 99%